If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7 + -1x)(pi + 2x) = 0 Multiply (7 + -1x) * (ip + 2x) (7(ip + 2x) + -1x * (ip + 2x)) = 0 ((ip * 7 + 2x * 7) + -1x * (ip + 2x)) = 0 ((7ip + 14x) + -1x * (ip + 2x)) = 0 (7ip + 14x + (ip * -1x + 2x * -1x)) = 0 (7ip + 14x + (-1ipx + -2x2)) = 0 Reorder the terms: (7ip + -1ipx + 14x + -2x2) = 0 (7ip + -1ipx + 14x + -2x2) = 0 Solving 7ip + -1ipx + 14x + -2x2 = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-14x' to each side of the equation. 7ip + -1ipx + 14x + -14x + -2x2 = 0 + -14x Combine like terms: 14x + -14x = 0 7ip + -1ipx + 0 + -2x2 = 0 + -14x 7ip + -1ipx + -2x2 = 0 + -14x Remove the zero: 7ip + -1ipx + -2x2 = -14x Add '2x2' to each side of the equation. 7ip + -1ipx + -2x2 + 2x2 = -14x + 2x2 Combine like terms: -2x2 + 2x2 = 0 7ip + -1ipx + 0 = -14x + 2x2 7ip + -1ipx = -14x + 2x2 Reorder the terms: 7ip + -1ipx + 14x + -2x2 = -14x + 14x + 2x2 + -2x2 Combine like terms: -14x + 14x = 0 7ip + -1ipx + 14x + -2x2 = 0 + 2x2 + -2x2 7ip + -1ipx + 14x + -2x2 = 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 7ip + -1ipx + 14x + -2x2 = 0 The solution to this equation could not be determined.
| 4-X^2= | | 4y-10=2 | | x^2+4x+m=0 | | 3r+6=-3 | | 3(5x-6)=-14x-7 | | 0.2x+3=8 | | -8+x=-8 | | 2n+4=26 | | x+1.5=4 | | x+1.5= | | 5x-2x=7x+2x-24 | | 6x+9=4x+21 | | 6A+2A=32 | | 6b-29=36 | | 4x^2-13x+5=-5x+2 | | x^2+5x+17=-5x+1 | | 3d-9-8b=11 | | x^2+7x-1=7 | | n^4-13n^2+36=0 | | 5g*4d= | | 11-8x=0 | | x^2+10x-27=8x-3 | | 5x-33=2x+57 | | =0.4(3d-5) | | -2y+3(-2)+5y+35=6y+2(-2)-3y+8 | | 2x+9y=4 | | 2(-2)-3+5y+6=8y-4(-2)+24 | | 3x+7y=6 | | 9(x-2)-4=14 | | -9x+3+5x=2x-3x+3+7-2 | | -x-2y+z=-6 | | 3x/7-5=4 |